1997
DOI: 10.1007/s001220050376
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance, coefficient of parentage, and genetic distance of six soybean populations

Abstract: Plant breeders would like to predict which biparental populations will have the largest genetic variance. If the population genetic variance could be predicted using coefficient of parentage or genetic distance estimates based on molecular marker data, breeders could choose parents that produced segregating populations with a large genetic variance. Three biparental soybean Glycine max (L.) Merr. populations were developed by crossing parents that were closely related, based on pedigree relationships. Three ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
13

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
3
25
0
13
Order By: Relevance
“…Findings on good correlations between the genetic distance of parents (from performance and molecular marker data) and the performance of their hybrids were similar to those reported in cacao and several species (Ghaderi et al, 1984;Shamsuddin, 1985;Cox and Murphy, 1990;Cruz et al, 1994;Ali et al, 1995;Diers et al, 1996;Xiao et al, 1996;Dias and Kageyama, 1997a;Kisha et al, 1997;Lanza et al, 1997;ManjarrezSandoval et al, 1997;Saghai Maroof et al, 1997;Burkhamer et al, 1998). However, there are several reports describing poor correlations (Vaillancourt et al, 1995;Cerna et al, 1997;Helms et al, 1997;Chowdari et al, 1998;Fabrizius et al, 1998;Perenzin et al, 1998;Tenkouano et al, 1998;Bohn et al, 1999;Joyce et al, 1999;Kidwell et al, 1999;Sant et al, 1999). Such contrasting results showed that association between parental divergence and heterosis remained an unsolved question.…”
Section: $Vvrfldwlrq Ehwzhhq Glvwdqfh Phdvxuhvsupporting
confidence: 69%
“…Findings on good correlations between the genetic distance of parents (from performance and molecular marker data) and the performance of their hybrids were similar to those reported in cacao and several species (Ghaderi et al, 1984;Shamsuddin, 1985;Cox and Murphy, 1990;Cruz et al, 1994;Ali et al, 1995;Diers et al, 1996;Xiao et al, 1996;Dias and Kageyama, 1997a;Kisha et al, 1997;Lanza et al, 1997;ManjarrezSandoval et al, 1997;Saghai Maroof et al, 1997;Burkhamer et al, 1998). However, there are several reports describing poor correlations (Vaillancourt et al, 1995;Cerna et al, 1997;Helms et al, 1997;Chowdari et al, 1998;Fabrizius et al, 1998;Perenzin et al, 1998;Tenkouano et al, 1998;Bohn et al, 1999;Joyce et al, 1999;Kidwell et al, 1999;Sant et al, 1999). Such contrasting results showed that association between parental divergence and heterosis remained an unsolved question.…”
Section: $Vvrfldwlrq Ehwzhhq Glvwdqfh Phdvxuhvsupporting
confidence: 69%
“…There was a week correlation (p < 0.05) for plant height in the F 2:9 generation, but the magnitude (0.44) is not useful in predicting the population genetic variances. Other studies carried out on soybeans show that the magnitude of the correlation between GD as estimated by molecular markers and GV depends on the population set and the environmental conditions under which the GV is estimated (Helms et al 1997;Kisha et al, 1997;Manjarrez-Sandoval et al, 1997).…”
Section: Resultsmentioning
confidence: 94%
“…In theory, genetic distance based on molecular markers has a greater potential for predicting the performance of soybean populations, but the literature shows an apparent dependence on the population set used (Helms et al, 1997;Kisha et al, 1997;Manjarrez-Sandoval et al, 1997). The study reported in the current paper was carried out to verify whether the genetic distance based on RAPD markers is useful for predicting the performance of soybean populations derived from two-way crosses for a set of parents that include adapted and non-adapted inbred lines, in a diallel scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in wheat (Triticum aestivum), oat (Avena sativa) and soybean (Glycine max) suggest that pedigree divergence between parents, estimated on the basis of the coefficient of parentage (Kempthorne, 1969), could be used to predict genetic variance in F 2 or later segregating generations (Bhatt, 1970(Bhatt, , 1973Cowen and Frey, 1987;Manjarrez-Sandoval et al, 1997). However, other studies in the same species (Moser and Lee, 1994;Helms et al, 1997;Kisha et al, 1997;Burkhamer et al, 1998;Bohn et al, 1999) indicated that the relationship between parental pedigree distance and progeny genetic variance was neither consistent nor strong enough to permit reliable prediction of genetic variance. One possible explanation for the limited relationship between pedigree divergence and progeny variance observed in these studies is that coefficients of parentage may be inaccurate because the parents of some specific crosses might differ for many genes affecting a trait.…”
Section: Introductionmentioning
confidence: 99%
“…Although GD estimates based on molecular marker estimates have been effective at grouping related germplasm (Melchinger et al, 1998), the relationship between GD in parents and genotypic variance components (GVCs) in their progenies has been reported as weak or non-significant across many studies (Helms et al, 1997;ManjarrezSandoval et al, 1997;Burkhamer et al, 1998;Melchinger et al, 1998;Bohn et al, 1999;Gumber et al, 1999;Brachi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%